Current Applications and Outcomes of Robotic Surgery in Pediatric Upper Airway and Neck Procedures: A Systematic Review - Irene Claudia Visconti; Marella Reale; Virginia Dallari; Eleonora M. C. Trecca; Antonella Miriam Di Lullo; Mario Turri-Zanoni; Michele Gaffuri (Children, 2025)
Objectives: This review summarizes current evidence on robotic-assisted upper airway and neck surgery in pediatric patients, highlighting clinical indications, outcomes, limitations, and areas for future research. Methods: A systematic review was conducted in accordance with PRISMA guidelines, including studies on robotic surgery for pediatric patients (≤18 years) with upper airway conditions and cervical pathologies. Data on study characteristics, patient demographics, surgical details, outcomes, and robotic system advantages or limitations were extracted. Results: Twenty studies met inclusion criteria, comprising 104 pediatric patients who underwent 110 robotic procedures, mostly transoral robotic surgery (TORS) for base of tongue, laryngeal, and cervical pathologies. The Da Vinci Si was the most used system. The mean operative time was ~74 min, with minimal blood loss and no intra/post operative tracheostomies. Reported advantages included enhanced visualization, precision, and reduced morbidity. Limitations involved size mismatches, limited working space, and high costs. Follow-up (mean 11.4 months) revealed no recurrences, confirming feasibility and safety in selected pediatric cases. Conclusions: Robotic-assisted surgery appears to be a feasible and safe option for managing pediatric upper airway and neck conditions, offering promising functional and aesthetic outcomes with low complication rates. However, its use is currently limited by anatomical constraints, high costs, and the need for surgeon training. Long-term prospective studies with larger cohorts are needed to confirm its efficacy and define its role compared to traditional techniques.